“It’s like they have two parents”: Consequences of inconsistent socialisation of Inuit children - Douglas, Anne (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2009)
Drawing on data collected in Arctic Bay (Nunavut) between 1990 and 1994, this article illustrates how school has incrementally intruded on the customary socialisation practices of Inuit families. Consequently, the full expression of Inuit personhood is diminishing. This damage is inevitable because school, an institution of mainstream Canadian society, promotes an expression of personhood that is inconsistent with its counterpart in Inuit society, which has traditionally socialised children to overcome egocentric concerns in the interest of group survival. In contrast, school socialises children for competitive individual survival in a wage economy. The different expectations for socially responsible behaviour in each context are particularly striking.